Design guidelines for routing protocols in ad hoc and sensor networks with a realistic physical layer. - Stojmenovic, Ivan (IEEE Communications magazine)
We present guidelines on how to design network layer protocols when the unit disk graph (UDG) model is replaced by a more realistic physical layer model. Instead of merely using the transmission radius in the UDG model, physical, MAC, and network layers share the information about a bit and/or packet reception probability as a function of distance between nodes. We assume that all nodes use the same transmission power for sending messages, and that a packet is received when all its bits are correctly received. The MAC layer reacts to this probabilistic reception information by adjusting the number of acknowledgments and/or retransmissions. We observe that an optimal route discovery protocol cannot be based on a single retransmission by each node, because such a search may fail to reach the destination or find the optimal path. Next, we discuss that gaining neighbor knowledge information with "hello" packets is not a trivial protocol. We describe localized position-based routing protocols that aim to minimize the expected hop count (in case of hop-by-hop acknowledgments and fixed bit rate) or maximize the probability of delivery (when acknowledgments are not sent). We propose a guideline for the design of greedy position-based routing protocols with known destination locations. The node currently holding the message forwards it to a neighbor (closer to the destination than itself) that minimizes the ratio of cost over progress, where the cost measure depends on the assumptions and metrics used, while the progress measures the difference in distances to the destination. We consider two basic medium access layer approaches, with fixed and variable packet lengths. This article serves as a preliminary contribution toward the development of network layer protocols that match the assumptions and criteria already used in simulators and ultimately in real equipment.